In vitro assessment of anti-tumorigenic mechanisms and efficacy of NanoALA, a nanoformulation of aminolevulic acid designed for photodynamic therapy of cancer - de Andrade, Laise Rodrigues; Primo, Fernando Lucas [UNESP]; da Silva, Jaqueline Rodrigues; Tedesco, Antonio Claudio; Lacava, Zulmira Guerrero Marques (Elsevier, 2017)
Background The development of nanocarriers is an important approach to increase the bioavailability of hydrophilic drugs in target cells. In this work, we evaluated the anti-tumorigenic mechanisms and efficacy of NanoALA, a novel nanoformulation of aminolevulic acid (ALA) based on poly(lactide-co-glycolide) (PLGA) nanocapsules designed for anticancer photodynamic therapy (PDT). Methods For this purpose, physicochemical characterization, prodrug incorporation kinetics, biocompatibility and photocytotoxicity tests, analysis of the cell death type and mitochondrial function, measurement of the intracellular reactive oxygen species production and DNA fragmentation were performed in murine mammary carcinoma (4T1) cells. Results NanoALA formulation, stable over a period of 90 days following synthesis, presented hydrodynamic diameter of 220 ± 8.7 nm, zeta potential of −30.6 mV and low value of polydispersity index (0.28). The biological assays indicated that the nanostructured product promotes greater ALA uptake by 4T1 cells and consequently more cytotoxicity in the PDT process. For the first time in the scientific literature, there is a therapeutic efficacy report of approximately 80%, after only 1 h of incubation with 100 μg mL−1 prodrug (0.6 mM ALA equivalent). The mitochondria are probably the initial target of treatment, culminating in energy metabolism disorders and cell death by apoptosis. Conclusions NanoALA emerges as a promising strategy for anticancer PDT. Besides being effective against a highly aggressive tumor cell line, the treatment may be economically advantageous because it allows a reduction in the dose and frequency of application compared to free ALA.
Keywords: Aminolevulic-acid (ALA); Mammary carcinoma; Nanocarriers; Photodynamic therapy (PDT); Poly(lactide-co-glycolide) (PLGA)